Eksplorasi Tren Penelitian Cloud Accounting melalui Analisis Bibliometrik - Mahardhika, Arya Samudra; Herwiyanti, Eliada; Lestari, Puji; Praptapa, Agung; Setyorini, Christina Tri; Suyono, Eko; Restianto, Yanuar Eko (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to understand the mapping and development of studies on cloud accounting by examining various articles from journals and proceedings. The method used in this research is qualitative with bibliometric analysis using R Studio and Biblioshiny. The data used consists of 100 articles published between 1994-2022, extracted from the Scopus database. The results indicate that the research cluster on this topic is very broad, but there are two relatively large clusters related to big data and cloud computing. There is a diverse distribution of author countries, with China being the most active in publishing articles, followed by Jordan, Turkey, the United States, and Bangladesh. Although this research provides valuable insights into the trends in cloud accounting research, limitations in data and methodology should be considered. However, overall, this study provides a comprehensive view of the development of cloud accounting research over the studied period.